B. Reyes Coria, Límites de la retórica clásica, México, UNAM, 2004, 176 págs. ISBN: 970-32-2141-6 (Minerva. Revista de Filología Clásica, 2019)
Reseña de B. Reyes Coria, Límites de la retórica clásica, México, UNAM, 2004, 176 págs. ISBN: 970-32-2141-6